2019
DOI: 10.1002/mgg3.751
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a de novo FOXP1 mutation and incidental discovery of inherited genetic variants contributing to a case of autism spectrum disorder and epilepsy

Abstract: Background Autism spectrum disorder is commonly co‐diagnosed intellectual disability, language disorder, anxiety, and epilepsy, however, symptom management is difficult due to the complex genetic nature of ASD. Methods We present a next‐generation sequencing‐based case study with both de novo and inherited genetic variants and highlight the impact of structural variants on post‐translational regulation of protein expression. Since management of symptoms has classically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…64 Epilepsy and autism spectrum diseases may result from a genetic variation-related de novo FOXP1 mutation. 65 The circ ANKMY2/miR106b-5p axis was found to be able to influence FOXP1 expression in this study. Additionally, the inhibition of FOXP1 restored the impacts of miR-106b-5p repression on the growth, formation of colonies, and programmed cell death in SK-N-AS cells.…”
Section: The Downregulation Of Foxo3a Mrna Expression In Tle Tissuesmentioning
confidence: 49%
See 1 more Smart Citation
“…64 Epilepsy and autism spectrum diseases may result from a genetic variation-related de novo FOXP1 mutation. 65 The circ ANKMY2/miR106b-5p axis was found to be able to influence FOXP1 expression in this study. Additionally, the inhibition of FOXP1 restored the impacts of miR-106b-5p repression on the growth, formation of colonies, and programmed cell death in SK-N-AS cells.…”
Section: The Downregulation Of Foxo3a Mrna Expression In Tle Tissuesmentioning
confidence: 49%
“…Additionally, in forebrain pyramidal neurons, FOXP1 controlled the expression of genes necessary for spatial cognition and synaptic flexibility 64 . Epilepsy and autism spectrum diseases may result from a genetic variation‐related de novo FOXP1 mutation 65 . The circ ANKMY2/miR106b‐5p axis was found to be able to influence FOXP1 expression in this study.…”
Section: Cerna Network In Epilepsymentioning
confidence: 54%
“…Li et al (2015) demonstrated that FOXP1 has vital influences on modulating neuronal migration and morphogenesis in cortical regions. FOXP1 mutations reportedly contribute to nervous system disorders including Huntington disease (Tang et al, 2012), autism (O'Roak et al, 2011;Chien et al, 2013), and epilepsy (Jay et al, 2019). In this study, FOXP1 exhibited an elevated tendency of expression in both MS and IS patients compared to controls (GSE21942: logFC = 1.21; GSE43591: logFC = 0.528; GSE16561: logFC = 0.15, and GSE58294: logFC = 0.34).…”
Section: Foxp1 Located At 3p13mentioning
confidence: 50%
“… Li et al (2015) demonstrated that FOXP1 has vital influences on modulating neuronal migration and morphogenesis in cortical regions. FOXP1 mutations reportedly contribute to nervous system disorders including Huntington disease ( Tang et al, 2012 ), autism ( O’Roak et al, 2011 ; Chien et al, 2013 ), and epilepsy ( Jay et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%